Implementasi Kurikulum Merdeka dalam Pembelajaran Pendidikan Pancasila: Tinjauan Kinerja Guru - Faisal Alam; Rahmat Iqbal; Sina Wardani Siregar; Sri Rahayu; Radiatul Adawiyah (Universitas Indraprasta PGRI, 2026)
The implementation of the Merdeka Belajar (Independent Learning) Curriculum in Indonesia has sparked a paradigm shift that requires teachers to adapt quickly and effectively in the learning process. This study aims to analyze the performance of elementary school teachers in implementing the Merdeka Curriculum in Pancasila Education for Grades I and IV, focusing on the aspects of planning, implementation, and evaluation. Employing a qualitative approach with a phenomenological design, the study involved teachers from SDN 053 Cisitu, SDN 208 Luginasari, and SDN 139 Sukarasa in Bandung City. Data were collected through direct observation, in-depth interviews, and the examination of instructional documents. The results indicate that teachers have been able to conduct learning in alignment with the principles and guidelines of the Merdeka Curriculum, including a sound understanding of the assessment structure. This achievement is supported by adequate school facilities and curriculum-related training. However, several challenges remain, such as limited learning media in non-driving schools and students’ difficulties in understanding the material. In response, teachers demonstrated creativity in developing teaching modules and maximizing the use of available learning media. This study underscores the need for continuous support, capacity building for teachers, and adaptive strategies to optimize the implementation of the Merdeka Curriculum, particularly in the teaching of Pancasila Education at the elementary school level.